2011
DOI: 10.1007/s10903-011-9478-1
|View full text |Cite
|
Sign up to set email alerts
|

Socioepidemiology of Cigarette Smoking Among Cambodian Americans in Long Beach, California

Abstract: We examined the prevalence of cigarette smoking among Cambodian Americans in Long Beach, California. A stratified random sample of 1,414 adult respondents was selected from 15 census tracts with high concentrations of Cambodian Americans. The prevalence of current smokers was 13.0%; the sex-specific prevalence of smoking was 24.4% for men and 5.4% for women. The mean age of the sample was 50.5 years; about 60% of the respondents were women. The survey response rate was 90.5% among households in which responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Other research has shown that subgroups not able to be included in this analysis, such as Cambodians and Samoans, exhibit concerning rates of tobacco use. 4,56 Future research on AA and NHPI tobacco use at the national level should be inclusive of the numerous racial/ethnic subgroups encompassing the AANHPI population and be powered sufficiently to detect meaningful by these variables.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has shown that subgroups not able to be included in this analysis, such as Cambodians and Samoans, exhibit concerning rates of tobacco use. 4,56 Future research on AA and NHPI tobacco use at the national level should be inclusive of the numerous racial/ethnic subgroups encompassing the AANHPI population and be powered sufficiently to detect meaningful by these variables.…”
Section: Discussionmentioning
confidence: 99%
“…11 For example, in Southeast Asia, betel quid chewing has been described in qualitative studies as being a "rite of passage into womanhood." 11,12 In Cambodia 10 and Myanmar, 6 household surveys indicate that about 17% of women use smokeless tobacco in the form of betel quid.…”
Section: Smentioning
confidence: 99%
“…Interventions might include increasing social and cultural acceptance of consistent implementation of smoking bans at home and in other settings, particularly among women, younger adults, and former smokers. Our findings may also have implications for interventions with other Asian populations, given high smoking rates among men and similar cultural norms (11). …”
Section: Discussionmentioning
confidence: 72%